Metabolism, excretion and pharmacokinetics of [14C]crizotinib following oral administration to healthy subjects. (January 2015) - Johnson, Theodore R.; Tan, Weiwei; Goulet, Lance; Smith, Evan B.; Yamazaki, Shinji; Walker, Gregory S.; O'Gorman, Melissa T.; Bedarida, Gabriella; Zou, Helen Y.; Christensen, James G.; Nguyen, Leslie N.; Shen, Zhongzhou; et al.
Abstract 1. Crizotinib (XALKORI®), an oral inhibitor of anaplastic lymphoma kinase (ALK) and mesenchymal-epithelial transition factor kinase (c-Met), is currently approved for the treatment of patients with non-small cell lung cancer that is ALK-positive. 2. The metabolism, excretion and pharmacokinetics of crizotinib were investigated following administration of a single oral dose of 250 mg/100 µCi [14C]crizotinib to six healthy male subjects. 3. Mean recovery of [14C]crizotinib-related radioactivity in excreta samples was 85% of the dose (63% in feces and 22% in urine). 4. Crizotinib and its metabolite, crizotinib lactam, were the major components circulating in plasma, accounting for 33% and 10%, respectively, of the 0–96 h plasma radioactivity. Unchanged crizotinib was the major excreted component in feces (∼53% of the dose). In urine, crizotinib and O-desalkyl crizotinib lactam accounted for ∼2% and 5% of the dose, respectively. Collectively, these data indicate that the primary clearance pathway for crizotinib in humans is oxidative metabolism/hepatic elimination. 5. Based on plasma exposure in healthy subjects following a single dose of crizotinib and in vitro potency against ALK and c-Met, the crizotinib lactam diastereomers are not anticipated to contribute significantly to in vivo activity; however, additional assessment in cancer patients is warranted.